2007
DOI: 10.1016/j.trsl.2006.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ambient particulate matter exposure on hemostasis

Abstract: Epidemiological studies have linked levels of particulate matter (PM) in ambient air to cardiovascular mortality and hospitalizations for myocardial infarction (MI) and stroke. Thrombus formation plays a primary role in potentiating acute cardiovascular events, and this study was undertaken to determine whether pulmonary exposure to PM alters hemostasis. PM was collected from the Chapel Hill, NC airshed and was administered to mice by intratracheal instillation at a dose previously shown to exacerbate myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 70 publications
(79 reference statements)
2
37
0
1
Order By: Relevance
“…54 Several studies have demonstrated an association between PM exposure and plasma PAI-1 levels in humans and in mice. 51,55 In this study, we detected only a slight increase of circulating PAI-1 but a 3-fold increase of the lung PAI-1 level after PM 2.5 exposure, indicating that the dose of PM 2.5 exposure (100 g/mouse) used in our studies is not sufficient to trigger systemic coagulation responses, but potent enough to induce localized lung pathologic changes. Although there was no significant difference in plasma PAI-1 levels between Sirt1 Ϫ/Ϫ and Sirt1 ϩ/ϩ littermates, lung PAI-1 level was higher in Sirt1 Ϫ/Ϫ mice after PM 2.5 treatment, indicating that Sirt1 deletion may lead to abnormal lung PAI-1 expression.…”
Section: Sirt1 Controls Lung Inflammation and Coagulation 2427mentioning
confidence: 50%
See 1 more Smart Citation
“…54 Several studies have demonstrated an association between PM exposure and plasma PAI-1 levels in humans and in mice. 51,55 In this study, we detected only a slight increase of circulating PAI-1 but a 3-fold increase of the lung PAI-1 level after PM 2.5 exposure, indicating that the dose of PM 2.5 exposure (100 g/mouse) used in our studies is not sufficient to trigger systemic coagulation responses, but potent enough to induce localized lung pathologic changes. Although there was no significant difference in plasma PAI-1 levels between Sirt1 Ϫ/Ϫ and Sirt1 ϩ/ϩ littermates, lung PAI-1 level was higher in Sirt1 Ϫ/Ϫ mice after PM 2.5 treatment, indicating that Sirt1 deletion may lead to abnormal lung PAI-1 expression.…”
Section: Sirt1 Controls Lung Inflammation and Coagulation 2427mentioning
confidence: 50%
“…15 It has been demonstrated that short-term PM exposure significantly decreased plasma TFPI level. 51 Decreased circulating TFPI levels have been linked to venous thrombosis 52 ; however, lung TFPI expression and regulation by Sirt1 after PM exposure have not been investigated. In this study, we demonstrated that lung TFPI expression was decreased after PM exposure, and Sirt1 deletion resulted in further reduction of TFPI levels in the lung, suggesting that Sirt1 could control coagulation responses by regulating TFPI expression.…”
Section: Sirt1 Controls Lung Inflammation and Coagulation 2427mentioning
confidence: 99%
“…341 Other findings also support potential procoagulant and thrombotic effects of PM. 342,343 These collective studies suggest that both short-and longterm PM inhalation can enhance thrombotic and coagulation tendencies, potentially via increases in circulating histamine and inflammatory cytokines and/or activated white cells and platelets. The plausibility of these pathways is supported by the well-recognized cross talk between inflammation and thrombosis.…”
Section: Thrombosis and Coagulationmentioning
confidence: 99%
“…Likewise, exposure of rats to concentrated PM from New York City air did not alter levels of fibrinogen, FVII or thrombin-antithrombin complexes (TAT) (Nadziejko et al 2002). Significant increases in the level of fibrinogen, or decreases in the levels of the anticoagulant proteins activated protein C or tissue factor pathway inhibitor (TFPI) upon short-term PM exposure have been observed in rodents, but at doses of 100 μg or higher per mouse (Cozzi et al 2007, Inoue et al 2006. One study stands out among other studies on procoagulant changes and PM exposure: Mutlu et al observed a pronounced prothrombotic phenotype in mice upon a single intratracheal instillation of as few as 10 μg of PM 10 , characterized by shortenings in bleeding time, PT and aPTT, and relatively high increases in the levels of circulating blood platelets, FVII, FVIII, FX and fibrinogen (Mutlu et al 2007).…”
Section: Pathophysiologymentioning
confidence: 99%
“…While studies, based on controlled exposure to diluted diesel exhaust , Carlsten et al 2007 or concentrated ambient particles (Ghio et al 2003), did not observe increases in the levels of plasminogen activator inhibitor-1 (PAI-1), some epidemiological or animal studies, focussing on urban PM, did: a study in 76 young healthy students demonstrated elevated PAI-1 concentrations in association with the mean PM 2.5 or PM 10 concentration at their university's campus over 1 to 3 days (Chuang et al 2007). Likewise, urban PM upregulated PAI-1 levels, 24 hours after intratracheal instillation in mice (Cozzi et al 2007). PM exposure could also impair the endothelial repair mechanisms by reducing the number of endothelial progenitor cells, as demonstrated by a recent report (O'Toole et al 2010).…”
Section: Endothelial Function and Fibrinolysismentioning
confidence: 99%